DETERMINANTS OF BRAND LOYALTY AT XYZ COFFEE SHOP: A STUDY OF GEN Z IN JAKARTA - Liman, Cindy Nathania; Ekawati , Sanny (Graduate Program of Universitas Tarumanagara, 2025)
This study’s purposes is to analyze the influence of brand experience, brand uniqueness, and perceived quality on brand loyalty of XYZ coffee outlet in Jakarta. The methodology used in this study is descriptive research design with a quantitative process. The sample selection technique used is a non-probability purposive sampling technique. A total of 125 respondents participated in the research through a google form questionnaire. This study utilizes the SmartPLS 4 software to analyse data, in which uses SEM analysis. The results of this study indicated that all of the factors positively and significantly influence brand loyalty. Those factors mentioned are brand experience, brand uniqueness, and perceived quality. This research plays a vital contribution to coffee vendors to further observe their brand uniqueness as a meaningful differentiation value for the customers when contrasted to other brand opposition. The product sold, in this case, must also perceive a great quality in terms of physical excellence and service in which will provide a unique experience for the customers and therefore create a loyalty to the coffee brand.